Colon Cancer: An Atypical Clinical Presentation - Urbina-Cabello, José Jesús; García-Sánchez, Morelos Adolfo; Méndez-Barrón, Gema; De La Fuente-González, Mireya; Flores-Pazos, Mauricio Israel; Hernández-Salvador, Judá Raquel; González-Valiente, Mariana; Romero-Guzmán, Elsa Nalleli; Ortiz-Ramirez, Mario Rogelio; Martínez-Gandarillas, Carlos Alberto; Cruz-Pacheco, Salomón (British Journal of Healthcare and Medical Research, 2023)
Introduction: Colon and rectal cancer are the third neoplasm in incidence and the second in mortality worldwide. In the United States of America, it is the second most common neoplasm and the incidence in Mexico is unknown, the prevalence and morbidity, as well as its mortality. Aim: Case report and literature review. Method: 74-year-old female in the emergency department. It presents with leukocytosis and systemic inflammatory response due to wall abscess, emergency surgery is performed, with the discovery of cecum tumor, multivisceral resection is performed. Satisfactory evolution and diagnosis of colon cancer. Discussion: The clinical presentation of colon and rectal cancer is so varied, it will depend on the anatomical site of the colon (right/left) or rectum, primary tumor, synchronism, age, anatomical differentiation or histological lineage. Right colon cancer due to its physiological characteristics tends to be more complex in terms of its timely diagnosis, with the intervals of signs and symptoms to a longer-term diagnosis. The technical objectives of a surgery with the intention of being curative must have the circumferential resection margin, the distance of healthy tissue from the tumor and the lymph node dissection, avoiding hemorrhage in the surgical dissection so as not to implant micro metastases. Conclusions: The form of clinical presentation of colon cancer can be very varied, masked or simulated by another disease, its rarity or very low incidence, evokes the group of researchers to make this experience known.